Perancangan Platform User Generated Content untuk Publikasi Sekolah inklusi - Junaedi, Fajar; Sukmono, Filosa Gita; Sudiwijaya, Erwan; Arifianto, Budi Dwi (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2023)
The Muhammadiyah Gamping Special School (SLB) in Sleman is an inclusive school founded in 2012. The Muhammadiyah Gamping SLB was built to facilitate a place of learning for children who have deficiencies or disabilities. The problems faced by SLB Muhammadiyah Gamping are not yet known to the public and have never been reported by the media. In fact, inclusive schools are a necessity for some members of society. The solution to the problems faced by SLB Muhammadiyah Gamping is to develop publications about the school's work through mass media. The science and technology used in this service are user-generated content technology and digital journalism. Activities were carried out with digital journalism workshops and operational assistance for user-generated content. Sustainability means that the school can continue to write news after the service is completed. The implementation results exceeded the target with 28 news stories, from the initial target of 12 news stories for the SLB Muhammadiyah Gamping journalism brand.